Psychophysiological differences between subgroups of social phobia. - Hofmann, S; Newman, MG; Ehlers, A; Roth, W (1995)
Individuals meeting criteria of the revised third edition of Diagnostic and Statistical Manual for Mental Disorders (American Psychiatric Association, 1987) for social phobia with a fear of speaking in front of people were subdivided into those with (n = 16) and without (n = 14) avoidant personality disorder (APD). These individuals and nonanxious controls (n = 22) spoke in front of a small audience while speaking time, subjective anxiety, fearful thoughts, and electrocardiographic and respiratory measures were recorded. Controls spoke for longer than either social phobia group. Those with social phobia and APD reported more subjective anxiety and more fear cognitions than the other two groups; phobic individuals without APD showed greater heart rates in the phobic situation than either social phobics with APD or controls. The latter two groups did not differ in heart rate. These results indicate incongruent subjective and heart rate responses to the feared situation. A similar pattern of results was found when participants were divided into generalized and specific social phobia groups.